Sofosbuvir and velpatasvir: a stellar option for patients with decompensated hepatitis C virus (HCV) cirrhosis - Chua, Joel V.; Kottilil, Shyam (Annals of Translational Medicine; Vol 4, Supplement 1 (October 31, 2016): Annals of Translational Medicine, 2016)
The treatment of hepatitis C virus (HCV) in patients with advanced liver disease has consistently been associated with higher failure rates and increase rates of adverse events (1,2). The advent of highly effective direct acting antiviral (DAA) therapy in the management of these difficult-to-treat chronic hepatitis C subpopulation has significantly improved sustained virologic response (SVR, absence of HCV RNA in plasma 12 weeks after cessation of therapy), while maintaining an excellent safety profile (3-5). Achieving SVR has resulted in reversal of the degree of fibrosis, reduction in the risk of hepatocellular carcinoma, lowers the rate of hepatic decompensation, and perhaps curtails the need for liver transplantation (2,6,7). However, lack of availability of a pan-genotypic regimen has limited our ability to expand HCV treatment beyond patients infected with genotype 1 thus far. In particular, there are limited options to treat patients with HCV genotype 3, especially with decompensated liver disease (8).